Street-working children in Latin America: a critical perspective - María Camila Pinzón-Segura (BMJ Publishing Group, 2024)
This article critically explores the complex realities faced by street-working children (SWC) in Latin America, highlighting historical and structural inequalities-such as coloniality, heteropatriarchy, and neoliberal capitalism-that perpetuate their marginalisation. Hegemonic public policies tend to focus narrowly on control, normalisation, and short-term relief, often neglecting the deeper systemic issues that sustain these vulnerabilities. This study calls for a shift towards alternative frameworks of public policy analysis that permit addressing the socio-political and cultural specificities of Latin America from a decolonial perspective. By incorporating affective, semiotic, and material dimensions, the Affective Interstice Theory provides analytical tools to understand how policy discourses not only shape the emotional and material experiences of those involved but also reinforce existing power structures. These insights reveal critical opportunities for resistance and transformative change, urging the development of policies that do more than address immediate needs-policies that actively dismantle the structural dynamics underpinning the marginalisation of SWC. The article underscores the need for contextualised approaches that engage with the complexity of local realities, offering a path towards more equitable and just policy outcomes across the region.